'Will ye no' come back again?': Population challenge and diaspora policy in Scotland. Issue 7 (11th April 2022) - Leith, Murray S.; Sim, Duncan
Abstract: Like many countries, Scotland has its population challenges, including a low birth rate and an ageing population. Some countries have sought to offset these challenges by the promotion of 'replacement immigration' or by economic policies to attract migrants. But, as part of the United Kingdom, Scotland lacks many of the policy levers available to promote wide‐ranging socioeconomic development and has no powers over immigration, as this is reserved to the U.K. Government. In this paper, we explore the potential for attracting members of the Scottish diaspora as a means of boosting population growth, using data from a series of surveys we have undertaken during the last decade. Although Scotland's quality of life may be attractive to returners, employment opportunities are crucial. However, the coronavirus pandemic has shown the potential for widening home‐based working and this demonstrates additional possibilities for returners to live in Scotland while working elsewhere.